ANALISIS PEMECAHAN MASALAH GEOMETRI BERDASARKAN TINGKAT BERPIKIR TEORI VAN HIELE DAN GENDER - Marlinda Indah Eka Budiarti; Faisal Eka Mahendra (Program Studi Pendidikan Matematika Universitas PGRI Kanjuruhan Malang, 2020)
Abstract: Due to difficulties in learning geometry, the teacher plays an important and active role in creating students who have good problem solving skills. The teacher also has to test the level of geometrical thinking of students based on Van Hiele's theory to find out the students understanding about geometry material, so the teacher can overcome the difficulties of students in learning geometry. This research is designed to explore and describe the process of geometry problem solving based on Van Hiele's theory. Therefore this research used descriptive exploratory. It used qualitative approach. The subject of this research is limited to University of Muhammadiyah Sorong students which obtained the level of visualization, analysis, informal deductive and will be analyzed based on the gender. Data of this research is 1) Geometry Van Hiele Test; 2) Problem Solving Test; 3) Interview. The conclusion of this research is: 1) At the level of male visualization thinking is to identify problem and determine goal using language problem. While at the level of women visualization, it reached on determining goal, ; 2) the level of male analysis thinking is able to pass five steps in problem solving by using own language but are less systematic. While level of female analysis thinking is able to pass five steps in problem solving systematically; 3) level of male deductive formal thinking is to pass five steps problem solving systematically and using own language. While level of female deductive formal thinking is able to pass five steps problem solving systematically and explaining by using own language.